Biological activity of the essential oil of Drimys winteri - Navarro, Myriam; Urrejola, Felipe; Espinoza, Misael; Silva, Simón; González, Sebastián; Utreras, Diego; Fernandez, Katia; Bravo, Jessica (Frontiers in Chemistry, 2024)
In the Chilean indigenous culture, the tree Drimys winteri (Winteraceae) Canelo is of great importance and is considered the sacred Mapuche tree. It has antibacterial and disinfectant properties and is used in the treatment of various diseases, such as fevers, ulcers, cancers, and respiratory tract problems. The essential oil obtained from D. winteri, DW_EO, is bioactive, possesses insecticidal and repellent properties against pests, and shows activity toward plant growth regulators. It also has a phytotoxic effect against the growth and germination of weeds. The essential oil obtained from the leaves and bark of Drimys winteri has demonstrated antifungal, immunomodulatory, anti-inflammatory, and anticancer properties in in vitro and in vivo studies. It also possesses antioxidant activity and antibacterial effects. The essential oil contains monoterpenes such as zafrol, pinenes, and linalool, among others, that contribute to its bioactivity. The DW_EO and bioactive compounds have great potential in various applications in medicine, industrial food, sanitizer, and other areas.